2022
DOI: 10.3389/fmicb.2022.863325
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Chemical Fertilizer Combined With Bio-Organic Fertilizer Affects the Soil Microbial Community and Yield and Quality of Lettuce

Abstract: Reducing chemical fertilizers in combination with bio-organic fertilizers can limit the use of chemical fertilizers while maintaining soil fertility. However, the effects of combined fertilization on soil chemical properties, microbial community structure, and crop yield and quality are unknown. Using high-throughput sequencing, we conducted field experiments using lettuce plants subjected to five fertilization treatments: chemical fertilizer with conventional fertilization rate (CK), chemical fertilizer reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 93 publications
(98 reference statements)
2
37
0
Order By: Relevance
“…Previous studies have confirmed that additional bacterial fertilizers can reduce nitrate concentration in vegetables, such as lettuce and tomato (Brunetti et al, 2019;Jiang et al, 2019;Jin et al, 2022). Jin et al (2022) pointed out the application of B. subtilis bioorganic fertilizer enriched organic matter concentration in the plant-body, which increased the quality of lettuce. Similar results were observed in the present study, where soluble sugar and protein levels were increased to varying degrees in the BF group.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have confirmed that additional bacterial fertilizers can reduce nitrate concentration in vegetables, such as lettuce and tomato (Brunetti et al, 2019;Jiang et al, 2019;Jin et al, 2022). Jin et al (2022) pointed out the application of B. subtilis bioorganic fertilizer enriched organic matter concentration in the plant-body, which increased the quality of lettuce. Similar results were observed in the present study, where soluble sugar and protein levels were increased to varying degrees in the BF group.…”
Section: Discussionmentioning
confidence: 93%
“…Zhao et al (2019) reported that the application of bioorganic fertilizer including Bacillus could reshape the soil microbial community and promote pepper growth. It was shown that the application of Bacillus bioorganic fertilizer could be a sustainable pathway to improve soil nutrient utilization as well as increase the yield and quality of lettuce (Jin et al, 2022). In addition, Bacillus bioorganic fertilizer has recently been applied in the cultivation of economic crops, and the results show that it could stimulate microbial activity, inhibit banana Fusarium wilt disease and enhance the stress resistance of sorghum (Wu et al, 2019;Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The content of K + , Ca 2+ , Mg 2+ , and Na + ions was determined by the method referenced to Jin et al (2022). Cucumber leaves to be tested were taken, dried and crushed, passed through a 0.25 mm sieve, and the dried leaf material (0.5 g) was decocted with sulfuric acid and hydrogen peroxide.…”
Section: Determination Of Mineral Element Contentmentioning
confidence: 99%
“…Regarding the impact of synthetic fertilizers on communities of soil fungi, prior studies have reported that synthetic N application can decrease soil fungal biomass diversity and change fungal populations (Gomiero et al, 2011 ). Furthermore, the use of synthetic fertilizers alters fungal community structure and decreases external mycelium arbuscular mycorrhizal of soil fungi, whereas the use of organic fertilizers increases it (Paungfoo-Lonhienne et al, 2015 ; Jin et al, 2022 ). Alternatively, organic manure fertilization (i.e., farmyard and green manure) improves soil structure and fertility by increasing soil nutrient availability and organic matter (Zhang et al, 2021 ; Ali et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%